"Axis Libri" National Book Festival (Confluenţe Bibliologice, 2017)
The author reports about the cultural event ,,Axis Libri" National Book Festival, organized by „V.A. Urechia” County Library from Galati. The main purpose of this event was to give Galaţi people the opportunity to view and browse the choice of 10,000 book titles edited at over 250 publishers. The event was accompanied by book launches, conferences, debates, all made for a single purpose - highlighting the cultural heritage represented by the printed book.
Keywords: book festival